Effect of Manpower Factor on Semiautomatic Production Line Completion Time: A System Dynamics Approach - Ahmarofi, Ahmad Afif; Abidin, N. Z.; Ramli, Razamin (UMP Publisher, 2017)
Completion time in a manufacturing sector is the time required to complete a product in sequence process during production operation. In a semiautomatic production line, manpower factors such as fatigue and pressure are two significant influences on completion time. However, it is found that previous studies lack the concern to include manpower factor in completion time. Hence, this paper develops a causal loop diagram and stock flow diagram to simulate the influence of manpower factor on the completion time in a semiautomatic production line. In this research, a well-known audio speaker manufacturer is selected as a case company. As a result, it is found that the preparation time for materials has a great impact on fatigue and pressure as it contributes the highest percentage of deviation from the completion time base run with 72.22%. Finally, a policy regarding completion time improvement is recommended to the management to enhance their production performance